Exploring Identity and Agency through the Investment of Mexican Speakers of English as a Foreign Language - Zavala, Susie (Verbum et Lingua: Didáctica, lengua y cultura, 2020)
This article explores identity and agency through the concept of investment as it pertains to Mexican speakers of English as a second language. In this study, I revisit Bonny Norton’s concept of investment, and I claim that the concept of investment provides unique insights into local Mexican foreign-language learning practices. In this article, I argue that participants in my study are successful in their English language learning and language use when they take control of their own learning and use it for their own purposes. I conducted this research in a qualitative study employing semi-structured interviews using narrative analysis. This article will explain the concepts of investment and agency, articulate the overall methodology, and analyze the results of the five participants providing key conclusions to this study. By studying when and why Mexican speakers of English as a foreign language invest in English, this research can help educators understand these learners better. According to the study’s results, when English language learners take control of their own learning and language, using it for their own purposes, they are successful on their own terms.